Analysis of heterosis components and prediction of hybrid means based on intergroup topcrosses in maize - Moreira Júnior,Weber Neves (2022)
Abstract Diallel designs are widely used in plant breeding to select parents and to study trait inheritance. The present work aimed to present a method to evaluate two divergent groups of parents, in which one group is used as a tester of the contrasting group. Each parent is crossed with a balanced mixture of seeds from the parents of the other group, and the parents and topcrosses are experimentally evaluated. Two groups of ten inbred maize lines were used to obtain intergroup topcrosses and biparental crosses in a diallel scheme. The data were subjected to analysis of variance and parameter estimation using the two models. The results showed the reliability of the method for the evaluation of lines and prediction of means of hybrid populations and can be recommended when the number of parents to be evaluated is large, making it difficult to evaluate biparental crosses in a diallel scheme.